Business model of economic entities: bibliometric analysis - Bezverkhyi , Kostiantyn; Matiukha , Mykola (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
Modern transformation processes in the economy necessitate a rethink of the role of business models in developing business entities' strategies. A business model is a tool that combines an enterprise's resource potential with market opportunities to ensure the creation, preservation and distribution of value between stakeholders. Studying it in a global scientific context enables us to identify key trends and directions in the evolution of the concept.Problem statement. Despite the significant number of scientific works devoted to the structure and typology of business models, there is a lack of systematic understanding of the dynamics of this concept's development in international scientific discourse. The relationship between business models, digital transformation, innovation, and the sustainable development of enterprises remains insufficiently generalised.Unresolved aspects of the problem. Evolutionary approaches to the formation of business models and the identification of leading research clusters and relevant scientific research directions in this area require clarification. The comparative analysis of publications according to the leading scientometric databases, Scopus and Web of Science, has not been sufficiently researched.Purpose of the article. The article aims to provide a bibliometric and bibliographic analysis of scientific research in the field of business models for business entities.Presentation of the main material. The research was carried out using bibliometric, trend, cluster and content analysis. The bibliometric sample was formed using the Scopus (9,041 publications) and Web of Science (5,010 publications) databases. Maps of term co-use were constructed using the VOSviewer software and key scientific clusters representing the main areas of research in the field of business modelling were identified.Conclusions. The dominant areas of research were established to be the digitalisation of business processes, innovative models of value creation, and the sustainable development of enterprises. A shift in scientific interest from the theoretical description of business models to their application in the digital economy was revealed. The study's practical significance lies in its potential to inform effective enterprise development strategies and enhance the scientific and analytical tools used to study business models.